Cognitive Strategies Dependent on the Hippocampus and Caudate Nucleus in Human Navigation: Variability and Change with Practice - Iaria, Giuseppe; Petrides, Michael; Dagher, Alain; Pike, Bruce; Bohbot, Veronique D (The Journal of neuroscience, 2003)
The human brain activity related to strategies for navigating in space and how it changes with practice was investigated with functional magnetic resonance imaging. Subjects used two different strategies to solve a place-learning task in a computer-generated virtual environment. One-half of the subjects used spatial landmarks to navigate in the early phase of training, and these subjects showed increased activation of the right hippocampus. The other half used a nonspatial strategy and showed, with practice, sustained increased activity within the caudate nucleus during navigation. Activation common to both groups was observed in the posterior parietal and frontal cortex. These results provide the first evidence for spontaneous variability and shift in neural mechanisms during navigation in humans.